CORPUS LINGUISTICS IN UZBEKISTAN: CURRENT STATE, CHALLENGES, AND PROSPECTS FOR UZBEK LANGUAGE RESEARCH (Ustozlar uchun, 2026)
This article investigates the development and current status of corpus linguistics in Uzbekistan, focusing on the construction, availability, and application of Uzbek-language corpora in linguistic research and language education. Using a mixed-methods approach that combines systematic review of existing corpora and published research with semi-structured interviews with ten Uzbek corpus linguists, the study identifies critical infrastructure gaps, methodological challenges, and institutional barriers that constrain the field. Results reveal that while several Uzbek corpora exist — including the Uzbek National Corpus and domain-specific sub-corpora — they remain significantly smaller and less annotated than comparable corpora for major world languages. Furthermore, corpus-based methods are underutilised in Uzbek linguistics pedagogy and applied language research. The article concludes with evidence-based recommendations for scaling corpus infrastructure, fostering interdisciplinary collaboration, and integrating corpus tools into university curricula. The findings contribute to the growing literature on corpus linguistics in under-resourced language contexts and provide a roadmap for Uzbek language technology development.